Characterization of unsteady distortion events for S-duct intakes under non-uniform inlet conditions - Migliorini, Matteo; Zachos, Pavlos K.; MacManus, David G. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
The use of convoluted intakes is expected to grow in novel aircraft configurations as designers seek to integrate more closely the propulsion system with the airframe. Previous research highlighted considerable unsteady flow distortions for S-duct configurations. However, most of the work was limited to the types of flow distortion inherently generated within the duct which reflects a relatively narrow range of aerodynamic conditions. In addition, the conditions of the flow distortion approaching the propulsion system is still not well understood due to the lack of experimental data and methods for unsteady distortion analysis. Recently, a novel analysis method was developed to consider the unsteady flow distortion from the perspective of an envisaged rotor blade through the exploitation of measurements with high-bandwidth Particle Image Velocimetry. In this study, and with this method, the aim is to provide a more advanced classification of unsteady distortion events based on the distribution of incidence on the envisaged rotor blades. This work can provide guidelines for methods to evaluate peak distortion levels under different inlet configurations for intake-engine integration assessments.